Strain-induced robust magnetic anisotropy and room temperature magnetoelectric coupling effect in epitaxial SmFeO3 film - Zhang, Jun; Xue, Wuhong; Su, Tiancong; Ji, Huihui; Yan, Zhi; Zhou, Guowei; Quan, Zhiyong; Xu, Xiaohong (Science China materials, 2020)
Rare-earth orthoferrite SmFeO 3 is an outstanding single-phase multiferroic material, holding great potential in novel low-power electronic devices. Nevertheless, simultaneous magnetic and ferroelectric orders as well as magnetoelectric (ME) coupling effect at room temperature (RT) in this system have not been demonstrated yet. In this study, epitaxial SmFeO 3 films were successfully prepared onto tensile-strain Nb-SrTiO 3 (Nb-STO) substrates by a pulsed laser deposition (PLD) method. Measurement results show that the films exhibit obvious ferromagnetic and ferroelectric orders at RT. Meanwhile, the magnetic anisotropy gradually changes from out-of-plane (OP) to in-plane (IP) direction with increasing film thickness, which is attributed to the variations of O 2p-Fe 3d hybridization intensity and Fe 3d-orbit occupancy caused by the strain-relaxed effect. Moreover, electrically driven reversible magnetic switching further proves that the SmFeO 3 films exhibit the RT ME coupling effect, suggesting promising applications in new-generation electric-write magnetic-read data storage devices.